Landscape Ecology applied to the study of the Atlantic Forest - Bem dos Santos, Eric; Rejane Magalhães de; Silva, Milena Dutra da (Journal of Environmental Analysis and Progress, 2023)
Understanding the metric and dynamic behavior of Atlantic Forest landscapes is of fundamental importance for planning and decision-making, especially regarding the recovery of degraded areas and the creation of public policies for biodiversity protection/conservation. From this perspective, landscape ecology is an extremely important tool. The aim of the study was to understand the forms and applications of landscape ecology in relation to studies in the Atlantic Forest. Regarding the methodology, this research should be classified as bibliographic, specifically a narrative literature review. The results bring definition, origin/evolution, calculations (area, edge, core, and proximity), and applications. It is concluded that landscape ecology should be understood as a new and promising area, the use of landscape metrics brings to the ouse approach of maps and satellite images, allowing a larger scale of the study, whether cartographic, spatial, and/or temporal, enabling visualization of the landscape in different perspectives and from the analysis of its phytogeographic structure.